Displays as a Material: A Route to Making Displays More Pervasive - Sweeney, David; Chen, Nicholas; Hodges, Steve; Grosse-Puppendahl, Tobias (IEEE Pervasive Computing Magazine, 2016)
The plummeting cost of TVs and computer monitors, widespread adoption of mobile devices, and advent of wearable devices means that there are now more digital displays than ever before. But these are still outnumbered by the vast array of non-digital displays in the world in the form of text and graphics permanently printed on various objects around us. Turning these static surfaces into dynamic displays offers several benefits, including improved awareness of and faster access to relevant information;1 more freedom in terms of display locations, which would improve ergonomics and aesthetics; and the potential for new, more personalized products with ever changing designs that can seamlessly blend into the surroundings.